Foundations for Self-Determination in Early Childhood: An Inclusive Model for Children With Disabilities. (May 2013) - Palmer, Susan B.; Summers, Jean Ann; Brotherson, Mary Jane; Erwin, Elizabeth J.; Maude, Susan P.; Stroup-Rentier, Vera; Wu, Hsiang-Yi; Peck, Nancy F.; Zheng, Yuzhu; Weigel, Cindy J.; Chu, Szu-Yin; McGrath, Greg S.; et al.
This article introduces the Early Childhood Foundations Model for Self-Determination and provides a rationale for the need to consider the foundations of self-determination behavior that begin early in life. This model is based on the premise that young children with disabilities benefit from a collaborative partnership between important adults in the lives of children to provide a supportive, stimulating, and coordinated environment between inclusive classrooms and home settings. Within partnership, the Foundations Model establishes the proposition that the basic foundational skills for developing self-determination in later life require young children with disabilities to gain skills in (a) choice-making and problem solving, (b) self-regulation, and (c) engagement. In this position paper, the authors review literature related to these three foundational constructs and present a rationale for use of the Foundations Model as a guide to developing systematic interventions to start young students with disabilities on the road to building a foundation for self-determination.